Mysterious journeys, episode III - Zimmerman, Ron; Jones Evan Jason; Lovett, Marcus (distributed by Discovery Channel Video ; distributed in the Philippines by MagnaVision, 2003)
Travel the Earth to visit the sites that have played host to alien visitors. Reports of extraterrestrial visitors span human history and have come from all corners of the globe. Some places such as Roswell, New Mexico, have based their entire identity around their brush with the intergalactic. Mysterious Journeys takes you to these locations and investigates the fascinating and eerie stories that surround them.